Modernisasi Tanpa Pembangunan Dalam Proyek Food Estate Di Bulungan Dan Merauke - Anggalih Bayu Muh. Kamin; Reza Altamaha (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Abstract: Transmigration has been related to efforts to boost food productivity. During the New Order era, transmigration was promoted in order to create cheap labor on large government-owned plantations. After the New Order period, transmigration was once again made to support  food program initiated through food estate project. This study wants to explore the paradox of the process of modernization of large-scale agriculture through a food estate project which turned out causing negative impacts for transmigrant farmers and local residents. This research is a literature study carried out by searching research reports, government documents, journal articles, and news from various media concerning the implementation of food estate. Data analysis was carried out through several stages, namely data reduction, data presentation, verification and conclusion drawing. This study has discovered how the large-scale agricultural modernization projects in Merauke and Bulungan is not an effort to support food security, but merely a broad-scale agribusiness expansion. The implementation of transmigration, basically, only serves as a support to ease the agribusiness expansion that takes place in Merauke and Bulungan. This study has proven the condition of food insecurity that must be faced by transmigrant farmers local residents affected by the project.